Impact of extreme magnetic fields on the QCD topological susceptibility in the vicinity of the crossover region - B. B. Brandt; G. Endrődi; J. J. Hernández Hernández; G. Markó (Journal of High Energy Physics)
Abstract We present the first determination of the topological susceptibility from lattice QCD in the presence of strong background magnetic fields. Our simulations employ 2+1 flavours of stout-improved staggered quarks with physical masses and cover a broad range of temperatures and magnetic field values. The results are extrapolated to the continuum limit using four different lattice spacings and an eigenvalue reweighting technique to reduce discretisation errors. For low temperatures, our calculations show an enhancement of the topological susceptibility due to the magnetic field, compatible with predictions from chiral perturbation theory. At high temperatures, we observe the impact of inverse magnetic catalysis on the susceptibility.